2020
DOI: 10.3390/ijerph17113870
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Symptoms and Family Support on the Association Between Homophobic Bullying and Sedative/Hypnotic Use among Gay and Bisexual Men in Taiwan: A Moderated Mediation Model

Abstract: Sedative/hypnotic use and homophobic bullying have become a big mental health concern for gay and bisexual men. However, few studies have investigated the mediators and moderators of the association between them. The current study aimed to build a conceptual model to estimate the mediating effect of emotional symptoms and the moderating effect of family support on this association among gay and bisexual men in Taiwan. A total of 500 gay or bisexual men were recruited for the study. Their history of homophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A previous study in Taiwan found that 38% and 32.6% of young adult gay and bisexual men reported experiences of victimization of traditional and cyber sexuality-related bullying, respectively, during childhood and adolescence [11]. Moreover, research in Taiwan has found that victimization of sexuality-related bullying during childhood and adolescence increased the risks of depression [12], anxiety [12], suicide [13], addictive substances [14,15], self-identity confusion [16], and low quality of life [17] in early adulthood. Hatzenbuehler (2009) provided evidence for their psychological mediation hypothesis, which stated that the aforementioned stress negatively affects the cognitive, regulatory, and social mechanisms in minorities [18].…”
Section: Sexual Orientation As a Moderator In The Hbmmentioning
confidence: 99%
“…A previous study in Taiwan found that 38% and 32.6% of young adult gay and bisexual men reported experiences of victimization of traditional and cyber sexuality-related bullying, respectively, during childhood and adolescence [11]. Moreover, research in Taiwan has found that victimization of sexuality-related bullying during childhood and adolescence increased the risks of depression [12], anxiety [12], suicide [13], addictive substances [14,15], self-identity confusion [16], and low quality of life [17] in early adulthood. Hatzenbuehler (2009) provided evidence for their psychological mediation hypothesis, which stated that the aforementioned stress negatively affects the cognitive, regulatory, and social mechanisms in minorities [18].…”
Section: Sexual Orientation As a Moderator In The Hbmmentioning
confidence: 99%
“…Research has shown that low family support is associated with suicidality, distress, depression, hopelessness, and substance use among LGB individuals [23,[30][31][32]. Family support also buffers the mediating effect of emotional symptoms in the association between homophobic bullying and sedative/hypnotic use among gay and bisexual men [33]. However, the findings of previous studies examining the association between family support and internalized homonegativity among LGB individuals have been mixed.…”
Section: Role Of Family Support In Internalized Homonegativity Among ...mentioning
confidence: 99%
“…LGB individuals have higher rates of suicidality [59,60], addictive substances use [61,62], problematic internet and smartphone use [63], poor quality of life [64,65], depression [66], and psychological inflexibility [67] compared with heterosexual ones in Taiwan. Therefore, mental health is an important issue warranted further study among LGB individuals in Taiwan.…”
Section: Mental Health Among Lgb Individuals In Taiwanmentioning
confidence: 99%